Impact resistant epoxy resin composition, prepreg and laminate

By adding ASA resin with a specific ratio and modified rubber masterbatch to the epoxy resin, the problem of insufficient impact resistance of epoxy resin is solved, and the material is low melt viscosity, excellent solvent resistance and high mechanical properties are achieved, and it is suitable for a variety of outdoor products.

CN119752102APending Publication Date: 2025-04-04GUANGDONG HINNO TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411881191.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing epoxy resins and ASA resins have problems such as insufficient impact resistance, high melt viscosity and poor solvent resistance in outdoor products, which limits their application scope.

Method used

Through the synergy between weathering epoxy resin, ASA resin and modified rubber masterbatch of specific ratios, an impact epoxy resin composition has been developed, with low melt viscosity, excellent solvent resistance, excellent weather resistance and excellent mechanical properties.

Benefits of technology

It has achieved the improvement of the comprehensive performance of the material, with high tensile strength, high bending strength and high impact strength, and is suitable for automotive parts shells, building materials and outdoor fitness equipment, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005198246050000121
    Figure BDA0005198246050000121
  • Figure BDA0005198246050000131
    Figure BDA0005198246050000131
  • Figure BDA0005198246050000132
    Figure BDA0005198246050000132
Patent Text Reader

Abstract

The present invention discloses an impact-resistant epoxy resin composition, a prepreg and a laminate. The composition includes the following components by mass: 100 parts of weather-resistant epoxy resin, 20 to 40 parts of acrylonitrile-styrene-acrylate copolymer, 10 to 30 parts of modified rubber masterbatch, 5 to 30 parts of curing agent, 0.1 to 1 part of accelerator, and 50 to 100 parts of solvent. Among them, the weather-resistant epoxy resin is selected from at least one of alicyclic epoxy resin and aliphatic epoxy resin, and the modified rubber masterbatch is basically prepared from 100 parts of ethylene-vinyl acetate rubber, 5 to 20 parts of styrene-maleic anhydride copolymer and 0.1 to 0.5 parts of peroxide. The present invention not only improves the impact resistance of epoxy resin materials through the synergistic effect of components such as weather-resistant epoxy resin, acrylonitrile-styrene-acrylate copolymer (ASA resin), and modified rubber masterbatch in a specific ratio, but also enables the material to obtain excellent comprehensive performance, with low melt viscosity, excellent solvent resistance, excellent weather resistance and excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of epoxy resin composite materials, and specifically relates to an impact-resistant epoxy resin composition, a prepreg and a laminate. Background Art

[0002] Outdoor products, such as automobile parts shells, various building materials, and outdoor fitness or leisure equipment, play an important role in our daily lives. These products not only have to meet basic practical functions, but also need to withstand various tests from nature for a long time, such as strong ultraviolet radiation, salt spray erosion, and frequent scratches. In such harsh environments, the material selection of outdoor products is particularly important. The ideal material should have excellent weather resistance to resist ultraviolet aging; strong mechanical strength to ensure the stability and safety of the structure; and excellent impact resistance to prevent damage caused by accidental collisions or falls.

[0003] Among the existing materials, epoxy resin is widely used due to its unique properties. Epoxy resin has a lower viscosity, which allows it to more easily penetrate and wet the bonded surface during processing, thereby achieving a tight bond. At the same time, epoxy resin also exhibits excellent mechanical strength and solvent resistance, which means that it can maintain structural integrity and stability when subjected to heavy pressure or exposed to certain solvents. However, despite these significant advantages of epoxy resin, its low impact resistance has become a shortcoming that cannot be ignored. In application scenarios that need to withstand large impact forces or dynamic loads, epoxy resin may not provide sufficient protection, thereby limiting its scope of application.

[0004] At the same time, acrylonitrile-styrene-acrylate copolymer (ASA resin for short), as another important polymer material, also occupies a place in the field of outdoor products. The molecular structure of ASA resin is relatively rigid and there is no unsaturated structure, which enables it to maintain good dimensional stability and thermal stability during processing. Therefore, ASA resin is widely used in the manufacture of products that need to withstand high temperatures and have excellent mechanical properties and weather resistance. For example, in the fields of automotive exterior trim, decorative panels for building exterior walls, and outdoor furniture, ASA resin has shown good application effects. However, ASA resin is not perfect. Its solvent resistance is relatively poor, which means that when exposed to certain solvents, the surface of ASA resin may swell, discolor or lose gloss, thereby affecting the aesthetics and service life of the product. In addition, the melt viscosity of ASA resin is relatively high, which increases the energy consumption cost during the processing process, especially when performing high-temperature processes such as extrusion and injection molding, the increase in energy consumption is particularly obvious.

[0005] In view of the limitations of epoxy resin and ASA resin, it is necessary to explore new material systems in order to reduce melt viscosity, improve solvent resistance and impact resistance while maintaining excellent weather resistance and mechanical strength, so as to meet the higher requirements of material performance for outdoor products. Summary of the invention

[0006] The present invention aims to overcome at least one defect in the prior art and provide an epoxy resin composition having low melt viscosity, excellent solvent resistance, excellent weather resistance and excellent mechanical properties (high tensile strength, high flexural strength and high impact strength).

[0007] In order to solve the above technical problems, the following technical solutions are adopted:

[0008] In the first aspect, an impact-resistant epoxy resin composition is proposed. The composition comprises the following components by mass: 100 parts of weather-resistant epoxy resin, 20 to 40 parts of acrylonitrile-styrene-acrylate copolymer, 10 to 30 parts of modified rubber masterbatch, 5 to 30 parts of curing agent, 0.1 to 1 part of accelerator, and 50 to 100 parts of solvent. Among them, the weather-resistant epoxy resin is selected from at least one of alicyclic epoxy resin and aliphatic epoxy resin, and the modified rubber masterbatch is basically prepared from 100 parts of ethylene-vinyl acetate rubber, 5 to 20 parts of styrene-maleic anhydride copolymer and 0.1 to 0.5 parts of peroxide.

[0009] This composition has excellent comprehensive performance through the synergistic effect of the components such as weather-resistant epoxy resin, acrylonitrile-styrene-acrylate copolymer (ASA resin), and modified rubber masterbatch in a specific ratio. It also has low melt viscosity, excellent solvent resistance, excellent weather resistance, and excellent mechanical properties (high tensile strength, high bending strength, and high impact strength), providing an ideal material choice for outdoor products such as automotive parts shells, various building materials, and outdoor fitness or leisure equipment. Among them, the weather-resistant epoxy resin, ASA resin, and modified rubber masterbatch do not contain unsaturated structures, thus giving the composition excellent weather resistance, which means that it can effectively resist the erosion of harsh environmental factors such as ultraviolet rays, ozone, extreme high and low temperatures, and salt spray, ensuring the long-term stability and service life of the material outdoors or under harsh conditions.

[0010] The combination of ASA resin and weather-resistant epoxy resin not only enhances the weather resistance of the composition, but also improves the overall mechanical properties of the material through its unique molecular structure. After the modified rubber masterbatch modified from ethylene-vinyl acetate rubber (EVM) is matched with ASA resin, it makes up for the defect of high melt viscosity of ASA resin and reduces the melt viscosity of the composition, which means that during the processing, the composition is easier to flow and shape, and can be processed into molded products by injection molding, extrusion, etc., which not only improves production efficiency, but also reduces energy consumption, making the composition more competitive in processing costs. After the EVM in the modified rubber masterbatch is modified with styrene-maleic anhydride copolymer (SMA) and peroxide, it increases the compatibility with ASA resin and weather-resistant epoxy resin, and at the same time improves the disadvantage of poor mechanical strength of EVM, so that the tensile strength of the composition increases instead of decreases.

[0011] A unique "island structure" is formed between the weather-resistant epoxy resin, ASA resin and modified rubber masterbatch. The epoxy resin, as a continuous phase, wraps the ASA resin and modified rubber masterbatch (islands) dispersed in it like an ocean. This structure enables the material to have excellent solvent resistance and mechanical properties at the same time, not only significantly improving the tensile strength and bending strength of the material, but more importantly, through the synergistic effect of ASA resin and modified rubber masterbatch, the impact resistance of the material is greatly improved. The excellent impact resistance of ASA resin and modified rubber masterbatch themselves, coupled with their good compatibility with epoxy resin, enables the impact energy to be effectively dispersed and absorbed, thereby protecting the material as a whole from damage.

[0012] Preferably, the content of vinyl acetate in the ethylene-vinyl acetate rubber is 40 to 80 wt%.

[0013] Preferably, the molar ratio of styrene to maleic anhydride in the styrene-maleic anhydride copolymer is (1-4):1.

[0014] Preferably, the peroxide is selected from at least one of dicumyl peroxide, dibenzoyl peroxide and di-tert-butyl peroxide.

[0015] Preferably, the preparation process of the modified rubber masterbatch is as follows: ethylene-vinyl acetate rubber, styrene-maleic anhydride copolymer and peroxide are first mixed at a temperature of 85-95°C and a rotation speed of 600-700rpm for 20-30min, and then extruded and granulated by an extruder with a temperature of 180-220°C, a temperature increasing from feeding to discharging, and a rotation speed of 20-50rpm. The mixing process can be carried out in a high-speed mixer, and the extruder is preferably a twin-screw extruder, and the temperature from feeding to discharging can be set to 180°C, 190°C, 200°C, and 220°C, respectively.

[0016] Preferably, the weather-resistant epoxy resin is selected from at least one of bis((3,4-epoxycyclohexyl)methyl)adipate, the polymerization product of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate and caprolactone, 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester, 4-vinyl-1-cyclohexene diepoxide, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, hexahydrophthalic acid diglycidyl ester, and 1,4-cyclohexanedimethanol bis(3,4-epoxycyclohexanecarboxylic acid) ester.

[0017] Preferably, the melt index of the acrylonitrile-styrene-acrylate copolymer is more than 20 g / 10 min as measured by ASTM D1238, or more than 15 g / 10 min or 7 cm as measured by ISO 1133. 3 / 10min, that is, the acrylonitrile-styrene-acrylate copolymer is preferably a model with high fluidity, such as LG Chemical LI911, Kumho Rili XC200, Chimei PW-997, etc.

[0018] Preferably, the curing agent is selected from at least one of aliphatic polyamine curing agents, aromatic amine curing agents, polyamide curing agents, and hydrazide curing agents. More preferably, the curing agent is selected from aliphatic polyamine curing agents or aromatic amine curing agents containing two or more amine groups in the molecular structure, such as 4,4'-diaminodiphenyl sulfone, p-aminodiphenylmethane, dicyandiamide, and the like.

[0019] Preferably, the accelerator is selected from at least one of 2-methylimidazole and 2-ethyl-4-methylimidazole.

[0020] Preferably, the solvent is selected from at least one of acetone, butanone, N,N-dimethylformamide, cyclohexanone, propylene glycol methyl ether, ethylene glycol methyl ether and toluene.

[0021] If necessary, without damaging the original properties of the composition, the above-mentioned impact-resistant epoxy resin composition may also be added with additives commonly used in the field, such as other thermosetting resins, thermoplastic resins, ultraviolet absorbers, antioxidants, flame retardants, coupling agents, fillers, surfactants, etc.

[0022] The impact-resistant epoxy resin composition can be prepared by the following method: 50 to 100 parts of solvent, 100 parts of weather-resistant epoxy resin, 20 to 40 parts of acrylonitrile-styrene-acrylate copolymer, 10 to 30 parts of modified rubber masterbatch, 5 to 30 parts of curing agent and 0.1 to 1 part of accelerator are sequentially added into a container and stirred evenly.

[0023] In a second aspect, an impact-resistant epoxy resin prepreg is provided, wherein the prepreg comprises a reinforcement and a resin matrix attached to the reinforcement, wherein the resin matrix is ​​made of the impact-resistant epoxy resin composition.

[0024] The composition used in the prepreg has excellent comprehensive properties through the synergistic effect of components such as weather-resistant epoxy resin, acrylonitrile-styrene-acrylate copolymer (ASA resin), modified rubber masterbatch, etc. in a specific ratio. It has low melt viscosity, excellent solvent resistance, excellent weather resistance and excellent mechanical properties (high tensile strength, high bending strength and high impact strength), and provides an ideal material choice for outdoor products such as automotive parts shells, various building materials, and outdoor fitness or leisure equipment.

[0025] The material of the reinforcement is not limited, and can be made of at least one of plant fiber, animal fiber, mineral fiber and synthetic fiber. Preferably, the reinforcement is selected from at least one of glass fiber cloth, glass fiber mat, glass fiber paper, unidirectional glass fiber, basalt fiber cloth, unidirectional basalt fiber, carbon fiber cloth, unidirectional carbon fiber, aramid cloth and aramid paper.

[0026] The impact-resistant epoxy resin prepreg can be prepared by the following method: impregnating the reinforcement with the impact-resistant epoxy resin composition and drying in an oven at 150±5° C. for 3±1 min.

[0027] In a third aspect, an impact-resistant epoxy resin laminate is provided, which comprises at least one impact-resistant epoxy resin prepreg.

[0028] The prepreg used in the above-mentioned laminated board has low melt viscosity, excellent solvent resistance, excellent weather resistance and excellent mechanical properties (high tensile strength, high bending strength and high impact strength). The laminated board produced therefrom can be used in outdoor products such as automotive parts housings, various building materials, and outdoor fitness or leisure equipment.

[0029] The above-mentioned impact-resistant epoxy resin laminate can be prepared by the following method: stacking the impact-resistant epoxy resin prepreg and other prepregs, or multiple impact-resistant epoxy resin prepregs, to form a laminate, covering both sides of the laminate with a PET release film, sending it into a fast press at 130°C to 180°C, increasing the pressure to 100psi to 400psi, and maintaining constant temperature and pressure for 10min to 30min, taking out the material, cooling it to room temperature, and then tearing off the PET release films on both sides.

[0030] Compared with the prior art, this solution has the following beneficial effects: This solution not only improves the impact resistance of epoxy resin materials, but also enables the material to obtain excellent comprehensive performance, with low melt viscosity, excellent solvent resistance, excellent weather resistance and excellent mechanical properties (high tensile strength, high bending strength and high impact strength), through the synergistic effect of components such as weather-resistant epoxy resin, acrylonitrile-styrene-acrylate copolymer (ASA resin), and modified rubber masterbatch in specific proportions, providing an ideal material choice for outdoor products such as automotive parts housings, various building materials, and outdoor fitness or leisure equipment. DETAILED DESCRIPTION

[0031] The present invention provides an impact-resistant epoxy resin composition, a prepreg and a laminate. The impact-resistant epoxy resin composition comprises the following components by weight: 100 parts of a weather-resistant epoxy resin, 20 to 40 parts of acrylonitrile-styrene-acrylate copolymer (ASA resin), 10 to 30 parts of a modified rubber masterbatch, 5 to 30 parts of a curing agent, 0.1 to 1 part of an accelerator, and 50 to 100 parts of a solvent.

[0032] The weather-resistant epoxy resin is selected from at least one of alicyclic epoxy resins and aliphatic epoxy resins, preferably at least one of bis((3,4-epoxycyclohexyl)methyl)adipate, the polymerization product of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate and caprolactone, 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester, 4-vinyl-1-cyclohexene diepoxide, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, hexahydrophthalic acid diglycidyl ester, and 1,4-cyclohexanedimethanol bis(3,4-epoxycyclohexanecarboxylic acid) ester.

[0033] The melt index of ASA resin is more than 20g / 10min according to ASTM D1238, or more than 15g / 10min or 7cm according to ISO 1133. 3 / 10min, that is, ASA resin preferably has high fluidity, such as LG Chemical LI911, Kumho Sunny XC200, Chimei PW-997, etc.

[0034] The modified rubber masterbatch is basically prepared from 100 parts of ethylene-vinyl acetate rubber, 5-20 parts of styrene-maleic anhydride copolymer and 0.1-0.5 parts of peroxide. The content of vinyl acetate in the ethylene-vinyl acetate rubber is preferably 40-80wt%; the molar ratio of styrene to maleic anhydride in the styrene-maleic anhydride copolymer is preferably (1-4):1; the peroxide is preferably at least one of diisopropylbenzene peroxide, dibenzoyl peroxide and di-tert-butyl peroxide. The preparation process of the modified rubber masterbatch can be: ethylene-vinyl acetate rubber, styrene-maleic anhydride copolymer and peroxide are first mixed at a temperature of 85-95°C and a rotation speed of 600-700rpm for 20-30min, and then extruded and granulated by an extruder with a temperature of 180-220°C, a temperature increasing from feeding to discharging, and a rotation speed of 20-50rpm. The mixing process can be carried out in a high-speed mixer, and the extruder is preferably a twin-screw extruder. The temperatures from feeding to discharging can be set to 180° C., 190° C., 200° C., and 220° C., respectively.

[0035] The curing agent is preferably at least one of an aliphatic polyamine curing agent, an aromatic amine curing agent, a polyamide curing agent, and a hydrazide curing agent, and more preferably an aliphatic polyamine curing agent or an aromatic amine curing agent containing two or more amine groups in the molecular structure, such as 4,4'-diaminodiphenyl sulfone, p-aminodiphenylmethane, dicyandiamide, etc.

[0036] The accelerator is preferably at least one of 2-methylimidazole and 2-ethyl-4-methylimidazole.

[0037] The solvent is preferably at least one of acetone, butanone, N,N-dimethylformamide, cyclohexanone, propylene glycol methyl ether, ethylene glycol methyl ether and toluene.

[0038] If necessary, without damaging the original properties of the composition, the above-mentioned impact-resistant epoxy resin composition may also be added with additives commonly used in the field, such as other thermosetting resins, thermoplastic resins, ultraviolet absorbers, antioxidants, flame retardants, coupling agents, fillers, surfactants, etc.

[0039] The impact-resistant epoxy resin composition can be prepared by the following method: 50 to 100 parts of solvent, 100 parts of weather-resistant epoxy resin, 20 to 40 parts of ASA resin, 10 to 30 parts of modified rubber masterbatch, 5 to 30 parts of curing agent and 0.1 to 1 part of accelerator are sequentially added into a container and stirred evenly.

[0040] The impact-resistant epoxy resin prepreg comprises a reinforcement and a resin matrix attached to the reinforcement, wherein the resin matrix is ​​made of the above-mentioned impact-resistant epoxy resin composition. The impact-resistant epoxy resin prepreg can be prepared by the following method: impregnating the reinforcement with the impact-resistant epoxy resin composition and drying in an oven at 150±5°C for 3±1min.

[0041] The impact-resistant epoxy resin laminate comprises at least one of the above-mentioned impact-resistant epoxy resin prepregs. The impact-resistant epoxy resin laminate can be prepared by the following method: stacking the impact-resistant epoxy resin prepreg and other prepregs, or stacking a plurality of impact-resistant epoxy resin prepregs to form a laminate, covering both sides of the laminate with a PET release film, feeding the laminate into a fast press at 130°C to 180°C, increasing the pressure to 100psi to 400psi, maintaining constant temperature and pressure for 10min to 30min, taking out the material, cooling it to room temperature, and tearing off the PET release films on both sides.

[0042] In order to allow those skilled in the art to better understand this solution, the solution is further described in detail below in conjunction with specific examples. The process methods used in the examples are conventional methods unless otherwise specified; the materials used are commercially available unless otherwise specified. Among them:

[0043] Weather-resistant epoxy resin: 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (Huntsman CY179), bis((3,4-epoxycyclohexyl)methyl)adipate (Daicel Celloxide 2081), polymerization product of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate and caprolactone (Hunan Binghang New Materials CF108128), 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester (Synasia S-186), 4-vinyl-1-cyclohexene diepoxide (Jiangsu Taitel TTA22), hexahydrophthalic acid diglycidyl ester (Tokyo Chemical Industry C1434), 1,4-cyclohexanedimethanol bis(3,4-epoxycyclohexanecarboxylic acid) ester (Jiangsu Taitel TTA 60).

[0044] ASA resin: ASA resin (Chimei PW-997), ASA resin (Kumho Sunny XC200).

[0045] Modified rubber masterbatch: homemade. The preparation process is as follows: by mass, 100 parts of EVM (LEVAMELT600 from Lanxess, Germany), 10 parts of SMA (Sartoma SMA2000P), and 0.2 parts of BPO (CAS#: 94-36-0) are put into a high-speed mixer and mixed for 25 minutes. The temperature of the high-speed mixer is 90°C and the speed is 700rpm to obtain a premix. The premix is ​​fed into a twin-screw extruder. The temperature of the twin-screw extruder from feeding to discharging is set to 180°C, 190°C, 200°C, and 220°C, respectively, and the speed is 30rpm. After extrusion and cutting, pellets are obtained, namely modified rubber masterbatch.

[0046] Curing agent: 4,4'-diaminodiphenyl sulfone (CAS#:80-08-0), p-aminodiphenylmethane (CAS#:101-77-9), dicyandiamide (CAS#:461-58-5).

[0047] Accelerator: 2-methylimidazole (CAS#: 693-98-1), 2-ethyl-4-methylimidazole (CAS#: 931-36-2).

[0048] Solvents: butanone (CAS#:78-93-3), acetone (CAS#:67-64-1), N,N-dimethylformamide (CAS#:68-12-2), cyclohexanone (CAS#:108-94-1), propylene glycol methyl ether (CAS#:107-98-2), ethylene glycol methyl ether (CAS#:109-86-4), toluene (CAS#:108-88-3).

[0049] Control: Bisphenol A epoxy resin (NPEL-128, Nan Ya Plastics Industry Co., Ltd.) EVM (LEVAMELT 600, LANXESS, Germany).

[0050] Example 1

[0051] In parts by mass, 80 parts of butanone, 100 parts of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, 30 parts of ASA resin (Chimei PW-997), 20 parts of modified rubber masterbatch, 20 parts of 4,4'-diaminodiphenyl sulfone and 0.5 parts of 2-methylimidazole were added to a container in sequence, and stirred evenly to obtain an impact-resistant epoxy resin composition.

[0052] 400 g / m2 was impregnated with the obtained impact-resistant epoxy resin composition. 2 The glass fiber cloth was dried in an oven at 150°C for 3 minutes to obtain an impact-resistant epoxy resin prepreg with a thickness of 0.4 mm.

[0053] Four sheets of the obtained impact-resistant epoxy resin prepreg were stacked into a laminate, and a PET release film was covered on each side of the laminate, and sent to a 150°C fast press, the pressure was increased to 200 psi, and after constant temperature and pressure for 15 minutes, the material was taken out, cooled to room temperature, and then the PET release films on both sides were torn off to obtain an impact-resistant epoxy resin laminate with a thickness of 1.6 mm.

[0054] Example 2

[0055] In parts by mass, 80 parts of butanone, 100 parts of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, 20 parts of ASA resin (Chimei PW-997), 20 parts of modified rubber masterbatch, 20 parts of 4,4'-diaminodiphenyl sulfone and 0.5 parts of 2-methylimidazole were added to a container in sequence, and stirred evenly to obtain an impact-resistant epoxy resin composition.

[0056] 400 g / m2 was impregnated with the obtained impact-resistant epoxy resin composition. 2 The glass fiber cloth was dried in an oven at 150°C for 3 minutes to obtain an impact-resistant epoxy resin prepreg with a thickness of 0.4 mm.

[0057] Four sheets of the obtained impact-resistant epoxy resin prepreg were stacked into a laminate, and a PET release film was covered on each side of the laminate, and sent to a 150°C fast press, the pressure was increased to 200 psi, and after constant temperature and pressure for 15 minutes, the material was taken out, cooled to room temperature, and then the PET release films on both sides were torn off to obtain an impact-resistant epoxy resin laminate with a thickness of 1.6 mm.

[0058] Example 3

[0059] In parts by mass, 80 parts of butanone, 100 parts of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, 40 parts of ASA resin (Chimei PW-997), 20 parts of modified rubber masterbatch, 20 parts of 4,4'-diaminodiphenyl sulfone and 0.5 parts of 2-methylimidazole were added to a container in sequence, and stirred evenly to obtain an impact-resistant epoxy resin composition.

[0060] 400 g / m2 was impregnated with the obtained impact-resistant epoxy resin composition. 2 The glass fiber cloth was dried in an oven at 150°C for 3 minutes to obtain an impact-resistant epoxy resin prepreg with a thickness of 0.4 mm.

[0061] Four sheets of the obtained impact-resistant epoxy resin prepreg were stacked into a laminate, and a PET release film was covered on each side of the laminate, and sent to a 150°C fast press, the pressure was increased to 200 psi, and after constant temperature and pressure for 15 minutes, the material was taken out, cooled to room temperature, and then the PET release films on both sides were torn off to obtain an impact-resistant epoxy resin laminate with a thickness of 1.6 mm.

[0062] Example 4

[0063] In parts by mass, 80 parts of butanone, 100 parts of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, 30 parts of ASA resin (Chimei PW-997), 10 parts of modified rubber masterbatch, 20 parts of 4,4'-diaminodiphenyl sulfone and 0.5 parts of 2-methylimidazole were added to a container in sequence, and stirred evenly to obtain an impact-resistant epoxy resin composition.

[0064] 400 g / m2 was impregnated with the obtained impact-resistant epoxy resin composition. 2 The glass fiber cloth was dried in an oven at 150°C for 3 minutes to obtain an impact-resistant epoxy resin prepreg with a thickness of 0.4 mm.

[0065] Four sheets of the obtained impact-resistant epoxy resin prepreg were stacked into a laminate, and a PET release film was covered on each side of the laminate, and sent to a 150°C fast press, the pressure was increased to 200 psi, and after constant temperature and pressure for 15 minutes, the material was taken out, cooled to room temperature, and then the PET release films on both sides were torn off to obtain an impact-resistant epoxy resin laminate with a thickness of 1.6 mm.

[0066] Example 5

[0067] In parts by mass, 80 parts of butanone, 100 parts of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, 30 parts of ASA resin (Chimei PW-997), 30 parts of modified rubber masterbatch, 20 parts of 4,4'-diaminodiphenyl sulfone and 0.5 parts of 2-methylimidazole were added to a container in sequence, and stirred evenly to obtain an impact-resistant epoxy resin composition.

[0068] 400 g / m2 was impregnated with the obtained impact-resistant epoxy resin composition. 2 The glass fiber cloth was dried in an oven at 150°C for 3 minutes to obtain an impact-resistant epoxy resin prepreg with a thickness of 0.4 mm.

[0069] Four sheets of the obtained impact-resistant epoxy resin prepreg were stacked into a laminate, and a PET release film was covered on each side of the laminate, and sent to a 150°C fast press, the pressure was increased to 200 psi, and after constant temperature and pressure for 15 minutes, the material was taken out, cooled to room temperature, and then the PET release films on both sides were torn off to obtain an impact-resistant epoxy resin laminate with a thickness of 1.6 mm.

[0070] Example 6

[0071] In parts by mass, 80 parts of butanone, 100 parts of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, 30 parts of ASA resin (Kumho Rili XC200), 20 parts of modified rubber masterbatch, 20 parts of 4,4'-diaminodiphenyl sulfone and 0.5 parts of 2-methylimidazole were added to a container in sequence, and stirred evenly to obtain an impact-resistant epoxy resin composition.

[0072] 400 g / m2 was impregnated with the obtained impact-resistant epoxy resin composition. 2 The glass fiber cloth was dried in an oven at 150°C for 3 minutes to obtain an impact-resistant epoxy resin prepreg with a thickness of 0.4 mm.

[0073] Four sheets of the obtained impact-resistant epoxy resin prepreg were stacked into a laminate, and a PET release film was covered on each side of the laminate, and sent to a 150°C fast press, the pressure was increased to 200 psi, and after constant temperature and pressure for 15 minutes, the material was taken out, cooled to room temperature, and then the PET release films on both sides were torn off to obtain an impact-resistant epoxy resin laminate with a thickness of 1.6 mm.

[0074] Example 7

[0075] In parts by mass, 50 parts of propylene glycol methyl ether, 100 parts of 4-vinyl-1-cyclohexene diepoxide, 25 parts of ASA resin (Kumho Rili XC200), 25 parts of modified rubber masterbatch, 25 parts of p-aminodiphenylmethane and 0.1 parts of 2-ethyl-4-methylimidazole were added to a container in sequence, and stirred evenly to obtain an impact-resistant epoxy resin composition.

[0076] 400 g / m2 was impregnated with the obtained impact-resistant epoxy resin composition. 2 The glass fiber cloth was dried in an oven at 150°C for 3 minutes to obtain an impact-resistant epoxy resin prepreg with a thickness of 0.4 mm.

[0077] Four sheets of the obtained impact-resistant epoxy resin prepreg were stacked into a laminate, and a PET release film was covered on each side of the laminate, and sent to a 150°C fast press, the pressure was increased to 200 psi, and after constant temperature and pressure for 15 minutes, the material was taken out, cooled to room temperature, and then the PET release films on both sides were torn off to obtain an impact-resistant epoxy resin laminate with a thickness of 1.6 mm.

[0078] Example 8

[0079] In a container, 90 parts of acetone, 100 parts of 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester, 35 parts of ASA resin (Kumho Rili XC200), 15 parts of modified rubber masterbatch, 10 parts of dicyandiamide and 1 part of 2-ethyl-4-methylimidazole were added in sequence by mass and stirred evenly to obtain an impact-resistant epoxy resin composition.

[0080] 400 g / m2 was impregnated with the obtained impact-resistant epoxy resin composition. 2 The glass fiber cloth was dried in an oven at 150°C for 3 minutes to obtain an impact-resistant epoxy resin prepreg with a thickness of 0.4 mm.

[0081] Four sheets of the obtained impact-resistant epoxy resin prepreg were stacked into a laminate, and a PET release film was covered on each side of the laminate, and sent to a 150°C fast press, the pressure was increased to 200 psi, and after constant temperature and pressure for 15 minutes, the material was taken out, cooled to room temperature, and then the PET release films on both sides were torn off to obtain an impact-resistant epoxy resin laminate with a thickness of 1.6 mm.

[0082] Example 9

[0083] In parts by mass, 60 parts of N,N-dimethylformamide, 100 parts of 1,4-cyclohexanedimethanol bis(3,4-epoxycyclohexanecarboxylate), 35 parts of ASA resin (Kumho Rili XC200), 25 parts of modified rubber masterbatch, 5 parts of p-aminodiphenylmethane and 1 part of 2-ethyl-4-methylimidazole were added to a container in sequence, and stirred evenly to obtain an impact-resistant epoxy resin composition.

[0084] 400 g / m2 was impregnated with the obtained impact-resistant epoxy resin composition. 2 The glass fiber cloth was dried in an oven at 150°C for 3 minutes to obtain an impact-resistant epoxy resin prepreg with a thickness of 0.4 mm.

[0085] Four sheets of the obtained impact-resistant epoxy resin prepreg were stacked into a laminate, and a PET release film was covered on each side of the laminate, and sent to a 150°C fast press, the pressure was increased to 200 psi, and after constant temperature and pressure for 15 minutes, the material was taken out, cooled to room temperature, and then the PET release films on both sides were torn off to obtain an impact-resistant epoxy resin laminate with a thickness of 1.6 mm.

[0086] Example 10

[0087] In a container, 80 parts by mass of toluene, 100 parts by mass of diglycidyl hexahydrophthalate, 25 parts by mass of ASA resin (Kumho Rili XC200), 25 parts by mass of modified rubber masterbatch, 15 parts by mass of p-aminodiphenylmethane and 0.1 parts by mass of 2-ethyl-4-methylimidazole were added in sequence, and the mixture was stirred evenly to obtain an impact-resistant epoxy resin composition.

[0088] 400 g / m2 was impregnated with the obtained impact-resistant epoxy resin composition. 2 The glass fiber cloth was dried in an oven at 150°C for 3 minutes to obtain an impact-resistant epoxy resin prepreg with a thickness of 0.4 mm.

[0089] Four sheets of the obtained impact-resistant epoxy resin prepreg were stacked into a laminate, and a PET release film was covered on each side of the laminate, and sent to a 150°C fast press, the pressure was increased to 200 psi, and after constant temperature and pressure for 15 minutes, the material was taken out, cooled to room temperature, and then the PET release films on both sides were torn off to obtain an impact-resistant epoxy resin laminate with a thickness of 1.6 mm.

[0090] Embodiment 11

[0091] In parts by mass, 100 parts of cyclohexanone, 100 parts of bis((3,4-epoxycyclohexyl)methyl)adipate, 35 parts of ASA resin (Kumho Rili XC200), 15 parts of modified rubber masterbatch, 25 parts of p-aminodiphenylmethane and 1 part of 2-ethyl-4-methylimidazole were added to a container in sequence, and stirred evenly to obtain an impact-resistant epoxy resin composition.

[0092] 400 g / m2 was impregnated with the obtained impact-resistant epoxy resin composition. 2 The glass fiber cloth was dried in an oven at 150°C for 3 minutes to obtain an impact-resistant epoxy resin prepreg with a thickness of 0.4 mm.

[0093] Four sheets of the obtained impact-resistant epoxy resin prepreg were stacked into a laminate, and a PET release film was covered on each side of the laminate, and sent to a 150°C fast press, the pressure was increased to 200 psi, and after constant temperature and pressure for 15 minutes, the material was taken out, cooled to room temperature, and then the PET release films on both sides were torn off to obtain an impact-resistant epoxy resin laminate with a thickness of 1.6 mm.

[0094] Example 12

[0095] In parts by mass, 70 parts of ethylene glycol methyl ether, 100 parts of a polymerization product of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate and caprolactone, 25 parts of ASA resin (Kumho Rili XC200), 15 parts of modified rubber masterbatch, 30 parts of dicyandiamide and 0.1 part of 2-ethyl-4-methylimidazole were added to a container in sequence, and stirred evenly to obtain an impact-resistant epoxy resin composition.

[0096] 400 g / m2 was impregnated with the obtained impact-resistant epoxy resin composition. 2 The glass fiber cloth was dried in an oven at 150°C for 3 minutes to obtain an impact-resistant epoxy resin prepreg with a thickness of 0.4 mm.

[0097] Four sheets of the obtained impact-resistant epoxy resin prepreg were stacked into a laminate, and a PET release film was covered on each side of the laminate, and sent to a 150°C fast press, the pressure was increased to 200 psi, and after constant temperature and pressure for 15 minutes, the material was taken out, cooled to room temperature, and then the PET release films on both sides were torn off to obtain an impact-resistant epoxy resin laminate with a thickness of 1.6 mm.

[0098] Comparative Example 1

[0099] 80 parts of butanone, 100 parts of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, 20 parts of modified rubber masterbatch, 20 parts of 4,4'-diaminodiphenyl sulfone and 0.5 parts of 2-methylimidazole were added to a container in sequence by mass and stirred evenly to obtain an impact-resistant epoxy resin composition.

[0100] 400 g / m2 was impregnated with the obtained impact-resistant epoxy resin composition. 2 The glass fiber cloth was dried in an oven at 150°C for 3 minutes to obtain an impact-resistant epoxy resin prepreg with a thickness of 0.4 mm.

[0101] Four sheets of the obtained impact-resistant epoxy resin prepreg were stacked into a laminate, and a PET release film was covered on each side of the laminate, and sent to a 150°C fast press, the pressure was increased to 200 psi, and after constant temperature and pressure for 15 minutes, the material was taken out, cooled to room temperature, and then the PET release films on both sides were torn off to obtain an impact-resistant epoxy resin laminate with a thickness of 1.6 mm.

[0102] Comparative Example 2

[0103] In parts by mass, 80 parts of butanone, 100 parts of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, 50 parts of ASA resin (Chimei PW-997), 20 parts of modified rubber masterbatch, 20 parts of 4,4'-diaminodiphenyl sulfone and 0.5 parts of 2-methylimidazole were added to a container in sequence, and stirred evenly to obtain an impact-resistant epoxy resin composition.

[0104] 400 g / m2 was impregnated with the obtained impact-resistant epoxy resin composition. 2 The glass fiber cloth was dried in an oven at 150°C for 3 minutes to obtain an impact-resistant epoxy resin prepreg with a thickness of 0.4 mm.

[0105] Four sheets of the obtained impact-resistant epoxy resin prepreg were stacked into a laminate, and a PET release film was covered on each side of the laminate, and sent to a 150°C fast press, the pressure was increased to 200 psi, and after constant temperature and pressure for 15 minutes, the material was taken out, cooled to room temperature, and then the PET release films on both sides were torn off to obtain an impact-resistant epoxy resin laminate with a thickness of 1.6 mm.

[0106] Comparative Example 3

[0107] In parts by mass, 80 parts of butanone, 100 parts of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, 30 parts of ASA resin (Chimei PW-997), 20 parts of 4,4'-diaminodiphenyl sulfone and 0.5 parts of 2-methylimidazole were added to a container in sequence, and stirred evenly to obtain an impact-resistant epoxy resin composition.

[0108] 400 g / m2 was impregnated with the obtained impact-resistant epoxy resin composition. 2 The glass fiber cloth was dried in an oven at 150°C for 3 minutes to obtain an impact-resistant epoxy resin prepreg with a thickness of 0.4 mm.

[0109] Four sheets of the obtained impact-resistant epoxy resin prepreg were stacked into a laminate, and a PET release film was covered on each side of the laminate, and sent to a 150°C fast press, the pressure was increased to 200 psi, and after constant temperature and pressure for 15 minutes, the material was taken out, cooled to room temperature, and then the PET release films on both sides were torn off to obtain an impact-resistant epoxy resin laminate with a thickness of 1.6 mm.

[0110] Comparative Example 4

[0111] In parts by mass, 80 parts of butanone, 100 parts of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, 30 parts of ASA resin (Chimei PW-997), 40 parts of modified rubber masterbatch, 20 parts of 4,4'-diaminodiphenyl sulfone and 0.5 parts of 2-methylimidazole were added to a container in sequence, and stirred evenly to obtain an impact-resistant epoxy resin composition.

[0112] 400 g / m2 was impregnated with the obtained impact-resistant epoxy resin composition. 2 The glass fiber cloth was dried in an oven at 150°C for 3 minutes to obtain an impact-resistant epoxy resin prepreg with a thickness of 0.4 mm.

[0113] Four sheets of the obtained impact-resistant epoxy resin prepreg were stacked into a laminate, and a PET release film was covered on each side of the laminate, and sent to a 150°C fast press, the pressure was increased to 200 psi, and after constant temperature and pressure for 15 minutes, the material was taken out, cooled to room temperature, and then the PET release films on both sides were torn off to obtain an impact-resistant epoxy resin laminate with a thickness of 1.6 mm.

[0114] Comparative Example 5

[0115] In parts by mass, 80 parts of butanone, 100 parts of bisphenol A epoxy resin, 30 parts of ASA resin (Chimei PW-997), 20 parts of modified rubber masterbatch, 20 parts of 4,4'-diaminodiphenyl sulfone and 0.5 parts of 2-methylimidazole were added to a container in sequence, and stirred evenly to obtain an impact-resistant epoxy resin composition.

[0116] 400 g / m2 was impregnated with the obtained impact-resistant epoxy resin composition. 2 The glass fiber cloth was dried in an oven at 150°C for 3 minutes to obtain an impact-resistant epoxy resin prepreg with a thickness of 0.4 mm.

[0117] Four sheets of the obtained impact-resistant epoxy resin prepreg were stacked into a laminate, and a PET release film was covered on each side of the laminate, and sent to a 150°C fast press, the pressure was increased to 200 psi, and after constant temperature and pressure for 15 minutes, the material was taken out, cooled to room temperature, and then the PET release films on both sides were torn off to obtain an impact-resistant epoxy resin laminate with a thickness of 1.6 mm.

[0118] Comparative Example 6

[0119] In parts by mass, 80 parts of butanone, 100 parts of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, 30 parts of ASA resin (Chimei PW-997), 20 parts of EVM, 20 parts of 4,4'-diaminodiphenyl sulfone and 0.5 parts of 2-methylimidazole were added to a container in sequence and stirred evenly to obtain an impact-resistant epoxy resin composition.

[0120] 400 g / m2 was impregnated with the obtained impact-resistant epoxy resin composition. 2 The glass fiber cloth was dried in an oven at 150°C for 3 minutes to obtain an impact-resistant epoxy resin prepreg with a thickness of 0.4 mm.

[0121] Four sheets of the obtained impact-resistant epoxy resin prepreg were stacked into a laminate, and a PET release film was covered on each side of the laminate, and sent to a 150°C fast press, the pressure was increased to 200 psi, and after constant temperature and pressure for 15 minutes, the material was taken out, cooled to room temperature, and then the PET release films on both sides were torn off to obtain an impact-resistant epoxy resin laminate with a thickness of 1.6 mm.

[0122] The performance tests were conducted on the compositions and laminates obtained in the above-mentioned embodiments and comparative examples, respectively. The test items included: 150°C melt viscosity test, simply supported beam impact strength test, tensile strength test, and flexural strength test before and after aging. The test results are shown in Tables 1 to 3.

[0123] 1. 150℃ melt viscosity test: refer to the standard "GB / T 25278-2010", place each composition at room temperature and dry for 24 hours to obtain a sample, add the sample into the barrel at a constant temperature of 150℃, wait for preheating for 1 minute, then start the test and calculate the melt viscosity.

[0124] 2. Simply supported beam impact strength test: refer to the standard "GB / T 1043.2-2018", prepare the sample according to "Specimen Type 1" in Table 1 of "GB / T 1043.1-2008", carry out "Vertical Test through Layers" according to the requirements of Section 6.3.2.2 of "GB / T 1043.1-2008", with a pendulum of 4J, test and record the simply supported beam impact strength of each laminate.

[0125] 3. Tensile strength test: refer to the standard "GB / T 3354-2014", the loading speed is 1mm / min, and the tensile strength of each laminate is tested and recorded.

[0126] 4. Aging test: According to "Method A, Cycle No. 4" in Table 4 of the standard "ISO 4892-3", each laminate is subjected to 28 cycles of aging test.

[0127] 5. Bending strength test: refer to the standard "GB / T 9341-2008", prepare samples according to the sample thickness of each embodiment and comparative example, test "sample position LN" according to the requirements of Section 6.2.2, and test and record the bending strength of the unaged and aged laminated boards respectively.

[0128] Table 1 Components, dosages and test results of Examples 1 to 6

[0129]

[0130]

[0131] Table 2 Components, dosages and test results of Examples 7 to 12

[0132]

[0133]

[0134] Table 3 Components, dosages and test results of Comparative Examples 1 to 6

[0135]

[0136] As shown in Tables 1 to 3, the epoxy resin composition and laminate prepared within the scope of this solution can obtain better comprehensive performance. Specifically, the 150°C melt viscosity of the impact-resistant epoxy resin composition is ≤212Pa*s, and the simply supported beam impact strength of the impact-resistant epoxy resin laminate with a thickness of 1.6mm prepared therefrom is ≥253kJ / m 2 , tensile strength ≥ 261MPa, flexural strength ≥ 559MPa, and the flexural strength decrease rate after aging ≤ 8.76%.

[0137] Compared with Example 1, the epoxy resin composition of Comparative Example 1 does not add ASA resin, which reduces the mechanical strength of the composition, resulting in a significant decrease in impact strength, tensile strength, and flexural strength. The epoxy resin composition of Comparative Example 2 adds an ASA resin exceeding the upper limit, which increases the melt viscosity of the composition, which is not conducive to subsequent processing. The epoxy resin composition of Comparative Example 3 does not add modified rubber masterbatch, which increases the melt viscosity of the composition, which is not conducive to subsequent processing. The epoxy resin composition of Comparative Example 4 adds modified rubber masterbatch exceeding the upper limit, which reduces the mechanical strength of the composition, resulting in a significant decrease in tensile strength and flexural strength. The epoxy resin composition of Comparative Example 5 replaces the weather-resistant epoxy resin with an equal amount of non-weather-resistant bisphenol A epoxy resin, causing the anti-aging performance of the composition to decrease significantly. The epoxy resin composition of Comparative Example 6 replaces the modified rubber masterbatch with a common EVM in an equal amount. (Compared with Comparative Example 3), although it can reduce the melt viscosity of the composition, it also causes the impact strength, tensile strength, flexural strength and weather resistance of the laminate to decrease, especially the tensile strength.

[0138] The impact-resistant epoxy resin composition proposed in this scheme uses modified rubber masterbatch (EVM modified by SMA and peroxide) to compound with weather-resistant epoxy resin and ASA resin, which greatly reduces the melt viscosity of the composition at 150°C for subsequent processing. Compared with common EVM, the modified rubber masterbatch greatly reduces the melt viscosity of the composition, and not only does it not cause a decrease in the impact strength, tensile strength, and flexural strength of the laminate, but it even has a positive impact on the impact strength, tensile strength, and flexural strength of the laminate.

[0139] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all implementation methods here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention shall be included in the protection scope of the claims of the present invention.

Claims

1. An impact-resistant epoxy resin composition, characterized in that: The composition comprises the following components in parts by mass: 100 parts of weather-resistant epoxy resin, 20 to 40 parts of acrylonitrile-styrene-acrylate copolymer, 10-30 parts of modified rubber masterbatch, 5-30 parts of curing agent, 0.1 to 1 part of accelerator, and 50-100 parts of solvent; The weather-resistant epoxy resin is selected from at least one of alicyclic epoxy resin and aliphatic epoxy resin, and the modified rubber masterbatch is basically prepared from 100 parts of ethylene-vinyl acetate rubber, 5-20 parts of styrene-maleic anhydride copolymer and 0.1-0.5 parts of peroxide.

2. The impact-resistant epoxy resin composition according to claim 1, characterized in that The content of vinyl acetate in the ethylene-vinyl acetate rubber is 40 to 80 wt %; and / or The molar ratio of styrene to maleic anhydride in the styrene-maleic anhydride copolymer is (1-4):1; and / or The peroxide is selected from at least one of dicumyl peroxide, dibenzoyl peroxide and di-tert-butyl peroxide.

3. The impact-resistant epoxy resin composition according to claim 2, characterized in that: The preparation process of the modified rubber masterbatch is as follows: ethylene-vinyl acetate rubber, styrene-maleic anhydride copolymer and peroxide are first mixed at a temperature of 85-95° C. and a rotation speed of 600-700 rpm for 20-30 minutes, and then extruded and granulated by an extruder with a temperature of 180-220° C., a temperature increasing from feeding to discharging, and a rotation speed of 20-50 rpm.

4. The impact-resistant epoxy resin composition according to any one of claims 1 to 3, characterized in that: The weather-resistant epoxy resin is selected from at least one of bis((3,4-epoxycyclohexyl)methyl)adipate, a polymerization product of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate and caprolactone, 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester, 4-vinyl-1-cyclohexene diepoxide, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, hexahydrophthalic acid diglycidyl ester, and 1,4-cyclohexanedimethanol bis(3,4-epoxycyclohexanecarboxylic acid) ester.

5. The impact-resistant epoxy resin composition according to any one of claims 1 to 3, characterized in that: The melt index of the acrylonitrile-styrene-acrylate copolymer measured according to standard ASTM D1238 exceeds 20 g / 10 min, or the melt index of the acrylonitrile-styrene-acrylate copolymer measured according to standard ISO 1133 exceeds 15 g / 10 min or 7 cm 3 / 10min.

6. The impact-resistant epoxy resin composition according to any one of claims 1 to 3, characterized in that: The curing agent is selected from at least one of aliphatic polyamine curing agents, aromatic amine curing agents, polyamide curing agents, and hydrazide curing agents.

7. The impact-resistant epoxy resin composition according to claim 6, characterized in that: The curing agent is selected from aliphatic polyamine curing agents or aromatic amine curing agents containing two or more amine groups in the molecular structure.

8. The impact-resistant epoxy resin composition according to any one of claims 1 to 3, characterized in that: The accelerator is selected from at least one of 2-methylimidazole and 2-ethyl-4-methylimidazole; and / or The solvent is selected from at least one of acetone, butanone, N,N-dimethylformamide, cyclohexanone, propylene glycol methyl ether, ethylene glycol methyl ether and toluene.

9. An impact-resistant epoxy resin prepreg, characterized in that: The prepreg comprises a reinforcement and a resin matrix attached to the reinforcement, and the resin matrix is ​​made of the impact-resistant epoxy resin composition according to any one of claims 1 to 8.

10. An impact-resistant epoxy resin laminate, characterized in that: The laminate comprises at least one impact resistant epoxy resin prepreg as claimed in claim 9.